Efecto de los fitoesteroles de semillas de lupinus mutabilis sweet “chocho”, sobre los niveles séricos de transaminasas en hiperlipidemia inducida en oryctolagus cunniculus var. nueva zelanda. - Pulido Paredes, Davis Efraín (2012)
The purpose of this study is to determine the effect of seed phytosterols Lupinus mutabilis Sweet on serum transaminase of Oryctolagus cunniculus var. New Zealand induced hyperlipidemia. To which we worked with 18 specimens of Oryctolagus cunniculus var. New Zealand “rabbits”, divided into 3 groups: control group, experimental group I and experimental group II, which were induced hyperlipidemia. The experimental groups I and II were given a treatment with phytosterols 10% and 20% respectively. Samples of serum transaminase levels were taken before and after the induction of hyperlipidemia and 15 and 30 days after the treatment. It was determined that there was no effect of phytosterols from seeds of Lupinus mutabilis Sweet on serum transaminase levels of Oryctolagus cunniculus var. New Zealand with hyperlipidemia induced